2021
DOI: 10.1145/3479600
|View full text |Cite
|
Sign up to set email alerts
|

Reflect, not Regret: Understanding Regretful Smartphone Use with App Feature-Level Analysis

Abstract: Digital intervention tools against problematic smartphone usage help users control their consumption on smartphones, for example, by setting a time limit on an app. However, today's social media apps offer a mix of quasiessential and addictive features in an app (e.g., Instagram has following feeds, recommended feeds, stories, and direct messaging features), which makes it hard to apply a uniform logic for all uses of an app without a nuanced understanding of feature-level usage behaviors. We study when and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Another way a platform might seek to learn about its position on a content manifold might be to directly ask users about how much unwanted time they spend on the platform, sometimes termed "regretful use" [4]. For instance, suppose a platform surveyed users to determine how much time they want to spend on the platform, and compare this to the actual amount of time they spend.…”
Section: Surveysmentioning
confidence: 99%
See 2 more Smart Citations
“…Another way a platform might seek to learn about its position on a content manifold might be to directly ask users about how much unwanted time they spend on the platform, sometimes termed "regretful use" [4]. For instance, suppose a platform surveyed users to determine how much time they want to spend on the platform, and compare this to the actual amount of time they spend.…”
Section: Surveysmentioning
confidence: 99%
“…Taken together, these differences imply that we should modify the model such that whether or not system 1 is active at step t depends not on the content consumed at the previous step, but on the properties of the d pieces of content recommended for consumption at step t + 1. 4 As before, we will assume that each piece of content has parameters (p, q, v). Denote the parameters of the d options presented to the user at step t as {(p i , q i , v i,t ) : i ∈ {1, .…”
Section: Extending the Model To Incorporate User Content Choicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-code development platforms have been defined, according to practitioners, to be ( User studies have shown that users can self-identify malevolent harms and habits upon self-reflection and develop desires to intervene against them [9,60]. Not only do end-users have a desire or interest in self-reflection, but there is indication that end-users have a willingness to act.…”
Section: Opportunities For Low-code Development In Interface Modifica...mentioning
confidence: 99%
“…An intersecting data source that enables both end-user self-reflection [9,60] and interface re-rendering via overlay [12] is the screen history or interface interaction history (denoted as screenome). Specifically, we can orchestrate a loop that receives input from users and generates outputs for users.…”
Section: Screenome Visualization and Low-code Developmentmentioning
confidence: 99%